A modified distiller's grains adsorbent, a preparation method and application thereof
Patent Information
- Application Number
- CN202311159908.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-08
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-09-08
AI Technical Summary
以至于一些酒厂在盲目的、不顾后果的扩大产能,然而白酒与酒糟废弃物的产量比为1:3至1:4,可见酒糟废弃物的产量之大,如处理不当将会对生态环境造成严重的威胁,且酒糟目前运用十分受限,仅在农业、饲养等少数行业有所利用,大部分酒糟废弃物被大量堆积和焚烧,这都会给自然环境造成十分严重的危害和影响,因此探寻一种合理地、科学地、无污染地、可持续性地和经济效益高地利用酒糟资源的技术十分重要
[0021]由酒糟为原料经过改性所制备出的吸附剂是一类吸附能力强、吸附效率高且重复使用能力强的吸附剂,将此吸附剂用于酿酒废水中重金属的去除上可以达到事半功倍的效果,符合经济发展的可持续性、符合生态系统的无污染性和企业要求的高经济效益。
Smart Images

Figure CN118079864B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of heavy metal adsorption technology, specifically to a modified adsorbent made from distiller's grains, its preparation method, and its application. Background Technology
[0002] Alcohol is becoming increasingly indispensable in people's daily activities and interpersonal interactions. With the rapid development of the social economy, the influence of the brewing industry is growing daily, and it is increasingly loved by the general public, leading to a surge in people's dependence on alcohol. This has resulted in some distilleries blindly and recklessly expanding their production capacity. However, the ratio of liquor production to waste lees is 1:3 to 1:4, demonstrating the enormous amount of waste lees produced. Improper handling will pose a serious threat to the ecological environment. Currently, the use of lees is very limited, with only a few sectors such as agriculture and animal husbandry utilizing it. Most of the lees waste is piled up and burned, causing severe damage and impact on the natural environment. Therefore, it is crucial to explore a technology for the rational, scientific, pollution-free, sustainable, and economically efficient utilization of lees resources.
[0003] However, the brewing process is highly specialized, producing wastewater that is extremely polluting. Direct discharge into the ecosystem will severely impact and damage both human living environments and the natural environment. Heavy metals, referring to metals with a density greater than 4.5 g / cm³, are particularly harmful and polluting substances in brewing wastewater. These are primarily lead, cadmium, and copper—metals that are highly hazardous, polluting, difficult to degrade, and can be transferred through the food chain. Long-term accumulation in the ecosystem will have adverse effects on humans and the ecosystem. Among all heavy metals, lead is the most harmful. Therefore, proper treatment of distiller's grains and brewing wastewater is of paramount importance.
[0004] Therefore, this application uses distiller's grains waste as raw material to prepare a modified adsorbent for adsorbing and removing heavy metals from brewing wastewater. Summary of the Invention
[0005] The present invention aims to provide a modified adsorbent made from distiller's grains, its preparation method and application, wherein the modified adsorbent is made from distiller's grains waste to adsorb and remove heavy metals from brewing wastewater.
[0006] To achieve the above objectives, the present invention provides the following technical solution:
[0007] A modified adsorbent made from distiller's grains is obtained through alkalization, oxidation, cross-linking, and exchange of groups.
[0008] A method for preparing a modified adsorbent from distiller's grains includes the following steps:
[0009] S1. Alkalization of distiller's grains: Take 200-300g of distiller's grains powder, prepare 1-1.5L of 0.1-0.2mol / L NaOH solution and add it to the distiller's grains powder. Stir at a constant temperature of 45-50℃ for 6-7h. Then add concentrated hydrochloric acid to adjust the pH to 7. Discard the supernatant, wash the precipitate until neutral and centrifuge. Discard the supernatant again, take out the precipitate, dry it at 45-50℃, and grind it into powder to obtain alkalized distiller's grains.
[0010] S2. Oxidation of distiller's grains: Mix 10-20g of alkalized distiller's grains with 50-100ml of anhydrous ethanol and stir at 45-50℃ for 1-1.5h to obtain an alkalized distiller's grains solution; prepare a sodium periodate solution by adding 5-10g of sodium periodate to 50-100ml of distilled water; add the sodium periodate solution dropwise to the alkalized distiller's grains solution and stir; then add hydrochloric acid to adjust the pH to 4.0 and stir at 45-50℃ for 24-36h; then add 5-10ml of ethylene glycol and stir before filtration to remove the solid; wash the residue after filtration with 50-100ml of anhydrous ethanol to obtain oxidized distiller's grains;
[0011] S3. Modification of distiller's grains: Take 2-5g of oxidized distiller's grains, add 30-50ml of anhydrous ethanol and stir for 2-3h, then add 2-3g of salicylhydrazine, add glacial acetic acid as a catalyst, stir at 45-50℃ for 24-36h, then filter and air dry to obtain modified distiller's grains.
[0012] S4. Crosslinking of distiller's grains: Add 0.5-0.8g of sodium alginate to 100-150ml of distilled water, then add 2-3g of modified distiller's grains and stir thoroughly. Then add 1-2mL of BDE crosslinking agent and stir for 12-15h. Freeze for 24-48h and then freeze dry under vacuum to prepare the crosslinked product of sodium alginate with hydrazone crosslinking.
[0013] S5. Adding groups through lees exchange: The cross-linked material is added to a 3-5% calcium chloride solution and stirred for 12-24 hours. After freezing and vacuum drying, the modified adsorbent is obtained.
[0014] Furthermore, in step S2, the alkalized distiller's grains and anhydrous ethanol are stirred in a light-protected environment, and the sodium periodate solution is prepared in a light-protected environment.
[0015] Furthermore, the constant temperature stirring uses a constant temperature magnetic stirrer.
[0016] Furthermore, after adding hydrochloric acid to adjust the pH in S2, the pH should be maintained at 4.0 during the constant temperature stirring process.
[0017] Furthermore, the filtration process utilizes a Buchner funnel.
[0018] Furthermore, in step S5, the freezing time is 12–24 hours, and the vacuum drying is performed using a vacuum dryer for 24–48 hours.
[0019] An application of a modified distiller's grains adsorbent for adsorbing heavy metals.
[0020] Working principle and beneficial effects of the present invention:
[0021] The adsorbent prepared by modifying distiller's grains is a type of adsorbent with strong adsorption capacity, high adsorption efficiency and strong reusability. Using this adsorbent to remove heavy metals from brewing wastewater can achieve twice the result with half the effort, which is in line with the sustainability of economic development, the pollution-free nature of the ecosystem and the high economic benefits required by enterprises. Attached Figure Description
[0022] Figure 1 This is a flowchart illustrating the preparation process of a modified adsorbent based on distiller's grains in this invention.
[0023] Figure 2 For JVS, OVS, JAD and JADPb 2 + Infrared spectrum;
[0024] Figure 3 For JVS(a), OVS(b), JAD(c), JADPb 2 SEM spectrum of +(d);
[0025] Figure 4 Thermogravimetric analysis plots of VS(a) and JAD(b);
[0026] Figure 5 Isoelectric plots of JAD at different pH values;
[0027] Figure 6 The graph shows the effect of JAD recycling on the adsorption rate.
[0028] Figure 7 JAD for Pb 2+ Langmuir and Freundlich model diagrams;
[0029] Figure 8 This is a graph showing the relationship between JAD adsorption time and adsorption rate.
[0030] Figure 9 The system fitting curves for the adsorption kinetics of Pb2+ by JAD. Detailed Implementation
[0031] The following detailed description illustrates the specific implementation method:
[0032] Example: A method for preparing a distillers' grains-modified adsorbent, comprising the following steps:
[0033] Alkalization of distiller's grains (VS): Take 200g of distiller's grains (VS) powder, add 1L of 0.1mol / L NaOH solution to the distiller's grains powder, stir at 45℃ using a constant temperature magnetic stirrer for 6h, then add concentrated hydrochloric acid dropwise to adjust the pH to 7, pour off some of the supernatant, pour the precipitate and an appropriate amount of distilled water into a beaker, wash until neutral, centrifuge, pour off the supernatant, remove the precipitate, dry at 45℃, grind into powder, and the alkalized distiller's grains (JVS) are obtained.
[0034] Oxidized and alkalized distiller's grains powder: Weigh 10g of alkalized distiller's grains (JVS) powder using an analytical balance. Add 50ml of anhydrous ethanol to a dark-colored bottle and stir with a magnetic stirrer at 45℃ for 1 hour. After stirring, weigh 5.0g of sodium periodate and add it to a second dark-colored bottle containing 50ml of distilled water to dissolve the sodium periodate. After dissolving, add it dropwise to the alkalized distiller's grains solution using a dropper. After adding the solution, stir for 15 minutes and adjust the pH to 4.0 with hydrochloric acid. Then stir with a magnetic stirrer at 45℃ for 24 hours, maintaining the pH at 4.0. After 24 hours, add 5ml of ethylene glycol and stir for 2 hours. Filter the solution using a Buchner funnel to remove the solid. Wash the residue in the Buchner funnel with 50ml of anhydrous ethanol to obtain oxidized distiller's grains (OJS). Then, place the solution in a fume hood for natural aging.
[0035] Modification of oxidized lees: Weigh 2g of dried oxidized lees, grind it into powder, and stir it with 30ml of anhydrous ethanol at room temperature for 2h. Then pour it into a round-bottom flask, weigh 2g of salicylhydrazine, add 5 drops of glacial acetic acid as a catalyst, and stir at 45℃ for 24h to obtain acylhydrazone compounds. Then filter it using a Buchner funnel. After filtration, place it in a natural fume hood to air dry for later use.
[0036] Modified distillers' grains crosslinked sodium alginate: Weigh 2g of air-dried modified distillers' grains and grind them into powder for later use. Add 100ml of distilled water to a beaker, then weigh 0.5g of sodium alginate and slowly add it to the beaker until the sodium alginate is completely dissolved. Then slowly add the prepared modified distillers' grains powder to the beaker until it is fully dissolved. Then add 1mL of BDE crosslinking agent and stir for 12h. Pour the mixture into a petri dish and freeze it for 24-48h. Then freeze-dry it under vacuum to prepare the crosslinked sodium alginate crosslinked with hydrazone.
[0037] Crosslinking material with Ca 2+Adding cross-linking groups: Weigh 3g of anhydrous calcium chloride into a beaker containing 97mL of pure water to prepare a 3% calcium chloride solution. Then add the acylhydrazone cross-linking agent and stir at low speed for 12 hours at room temperature. Spread evenly into a petri dish and freeze for 12-24 hours. Then vacuum dry for 24-48 hours to obtain the final adsorbent: modified distiller's grains adsorbent (JAD). Production process (e.g.) Figure 1 As shown in the figure.
[0038] The experimental method is as follows:
[0039] To investigate the optimal conditions under which JAD can adsorb lead from brewing wastewater under different environmental factors and conditions, this study employed a single-factor experimental method, using a Pb concentration of 1000 mg / L. 2+ The solution was used to represent the wastewater produced in the brewing process. An experimental variable was established as the basic condition, and appropriate amounts of Pb were collected each time according to the experimental plan. 2+ Solution, JAD added to Pb 2+ The adsorption experiment was performed in the solution at 180 r / min in a constant temperature shaking incubator. After shaking, the residual Pb in the filtrate was measured using an atomic absorption spectrophotometer. 2+ The concentration of JAD was used to analyze the effect of JAD on Pb in brewing wastewater. 2+ The removal rate Re is calculated using formulas 2-1 and 2-2:
[0040] R_e=(C_0-C_e) / C_0×100% (2.1)
[0041] q_e=(C_0-C_e) / W (2.2)
[0042] In the formula:
[0043] Pb before CO-JAD adsorption 2+ The initial concentration (mg / L);
[0044] Pb after Ce-JAD adsorption equilibrium 2+ The concentration at which equilibrium is reached (mg / L);
[0045] W — Mass of JAD added (mg).
[0046] To ensure the accuracy of the experiment, all experimental procedures were performed at least three times.
[0047] (1) Isopotential determination: In order to investigate the surface potential characteristics of JAD, 735 mg KCl was accurately weighed into a 100 mL beaker and stirred to dissolve. The solution was then transferred to a 100 mL volumetric flask and diluted with purified water. 10 mL of KCl solution was measured for each of the 7 groups. The pH of each group was adjusted to 1-7. 10 mg JAD was added to each group. The samples were placed in a constant temperature shaking incubator and the conditions were set to 25 °C and 180 r / min. The incubator was shaken for 6 h. After shaking, the pH of each group was measured again using a pH meter. The two sets of pH data measured for each group were used for isopotential analysis of JAD.
[0048] (2) Effect of pH on JAD adsorption performance: 100 mg / L of Pb was measured. 2+ Seven groups of 10 mL samples were prepared, with pH adjusted to 1, 2, 3, 4, 5, 6, and 7 using HCl and NaOH, respectively. 10 mg of JAD was added to each sample, and the samples were incubated at 25℃ and 18 r / min in a constant-temperature shaking incubator for 6 hours. After shaking, residual Pb was measured using an atomic absorption spectrophotometer. 2+ The concentration was used to investigate the effect of pH on the adsorption performance of modified distiller's grains.
[0049] (3)Pb 2+ Effect of concentration on JAD adsorption performance: Pb concentrations of 25 mg / L, 50 mg / L, 100 mg / L, 200 mg / L, 400 mg / L, 600 mg / L, 800 mg / L, and 1000 mg / L were measured. 2+ 10 mL of solution was mixed with 10 mg of JAD and the solution was shaken in a constant temperature shaker at 25 °C and 180 rpm for 6 h. After shaking, the Pb content in the solution was measured using an atomic absorption spectrophotometer. 2+ The concentration was used to investigate different Pb concentrations. 2+ The effect of concentration on JAD performance.
[0050] (4) Adsorption kinetics experiment: 150 mL of Pb with a concentration of 100 mg / L was measured. 2+ Solution, add 150mg,
[0051] JAD was adsorbed by shaking in a constant temperature shaking chamber at 25℃ and 180 r / min. Samples were taken at predetermined time points from 5 to 360 min, and the Pb content of the sampled solutions was measured using an atomic absorption spectrophotometer. 2+ The concentration was used to investigate the effect of dynamics on the performance of JAD.
[0052] (5) Adsorption thermodynamics experiment: Pb concentrations of 25 mg / L, 50 mg / L, 100 mg / L, 200 mg / L, 400 mg / L, 600 mg / L, 800 mg / L, and 1000 mg / L were measured.2+ Three groups of 10 mL solutions were prepared, each containing 10 mg of JAD. The solutions were then incubated at 25°C, 35°C, and 45°C at 180 rpm for 6 hours in a constant-temperature shaking incubator. After shaking, the Pb concentration in the solutions was measured using an atomic absorption spectrophotometer. 2+ The concentration was used to investigate the effect of temperature on the adsorption performance of JAD.
[0053] (6) Adsorption-desorption reuse experiment: A concentration of 200 mg / L Pb was measured. 2+ 200 mL of solution was added to 2 g of modified distiller's grains adsorbent, and the mixture was shaken in a constant temperature shaker at 25 °C and 180 r / min for 6 h. After shaking, the solution was filtered, and the residual Pb in the filtrate was measured using an atomic absorption spectrophotometer. 2+ The concentration of the filtered adsorbent was determined. The solution was added to 0.1 mol / L HCl and stirred at 25°C with a magnetic stirrer for 3 hours to allow for desorption. After desorption, the adsorbent was filtered, the pH was adjusted to 7, and after filtration, it was dried at 25°C for further adsorption of Pb. 2+ .
[0054] Experimental Results Analysis
[0055] ①Analysis of FT-IR scan results
[0056] FT-IR spectroscopy analysis can be used to explore the functional modification effect of JAD. Specifically, FT-IR spectrometry was used to determine the adsorption of Pb by JVS, OVS, JAD, and JAD. 2+ The adsorbent after (JADPb) 2+ Infrared absorption spectrum (e.g.) Figure 3-1 (As shown). Peaks at 3397, 3246, and 3251 cm⁻¹ appeared in the spectrum, caused by the stretching vibration of the CH single bond. Peaks at 2917, 2912, 2922, and 2926 in the figure are mainly due to the stretching vibration of the aldehyde group. The three single peaks at 1628, 1648, and 1643 in the figure are characteristic absorption peaks of the aldehyde carbonyl group in the OVS spectrum. This peak is due to the breaking of the C=C bond in the vicinal diol structure of the distiller's grains. The two significant peaks at 1582 and 1592 are caused by the stretching vibration of the C=N bond, while the NH stretching vibration produced two peaks at 1006 and 1002, indicating that the modification from OSA to JAD was successful and that the acylhydrazone group was successfully introduced into JAD. At the same time, it can be seen from the figure that OVS and JAD show multiple co-peaks, thus concluding that the functional modification synthesis from OVS to JAD was successful.
[0057] ②SEM and EDAX spectral analysis
[0058] Electron microscopy (SEM) was used to scan the adsorption of Pb by JVS, OVS, JAD, and modified distiller's grains adsorbent. 2+(JADPb 2+ The morphology before and after ( ) was studied and analyzed. Discoveries (such as...) Figure 2 (a) shows a rough surface with a small number of pores; the OVS surface (as shown in Figure 2(b)) has deposits and no voids; while the JAD surface (as shown in Figure 2(b)) has deposits and no voids; Figure 2 The structure shown in (c) has a surface morphology and size that varies greatly, with a large number of regularly shaped pores. It is precisely because of the irregular surface and the diversity of pore size structure that it is more conducive to the adsorption of Pb. 2+ In the adsorption of Pb 2+ After that, JAD (such as Figure 2 (d) The surface is more uniform and the pore structure is smaller. The analysis results show that after JAD adsorbs metallic lead, the structure of JAD is reconstructed.
[0059] The elemental composition of JAD before and after lead adsorption was analyzed by EDAX spectroscopy (as shown in Table 1), and the EDAX mapping diagrams before and after lead adsorption by JAD were also analyzed (as shown in Table 1). Figure 3 As shown in the diagram, JVS (such as...) Figure 3 (a) contains five elements: C, N, O, Na, and Ca, with contents of 52.17%, 7.45%, 38.28%, 0.63%, and 1.47%, respectively. From the OVS mapping diagram (as shown...) Figure 3 (b) shows that it contains only three elements: C, O, and Na, with contents of 50.62%, 48.23%, and 1.15%, respectively. From the JAD mapping diagram (as shown...) Figure 3 (c) The Ca content in the element is significantly increased, with C, N, O, and Ca contents of 28.96%, 8.90%, 47.09%, and 15.05%, respectively. Meanwhile, from JAPB... 2+ Mapping graph discovery (e.g.) Figure 3 As shown in (d), the elemental composition changed, with increased adsorption of Pb and a very low Ca content. The contents of C, N, O, Ca, and Pb were 40.38%, 5.09%, 29.27%, 0.10%, and 25.16%, respectively. Analysis of the EDAX test data shows that Na+ in OVS to JAD was completely converted to Ca. 2+ It was replaced because the presence of acylhydrazone groups in JAD restored the nitrogen content. JADPb 2+ Pb adsorbed 2+ And Ca 2+ However, it dropped to a very low level, indicating that Pb 2+ Replaced Ca 2+ Therefore, JAD is associated with Pb. 2+ The adsorption mechanism is the adsorption behavior caused by the ion exchange between lead and calcium elements on the JAD surface.
[0060] Table 1 - JVS, OVS, JAD, JADPb 2+ EDAX spectral parameters
[0061]
[0062] ③ Thermogravimetric analysis
[0063] To investigate the removal of Pb by JAD 2+ The stability of the lees before and after functional modification can be determined by the TG curve. Figure 4 (a) is the thermogravimetric analysis diagram of VS. Figure 4 (b) is the thermogravimetric analysis (TG) curve of JAD. From the TG curves of VS and JAD, it can be seen that: within the range of 35-150℃, both VS and JAD exhibited weight loss due to the removal of water, with JAD losing 0.846 mg less weight than VS; however, within the range of 150-240℃, JAD also exhibited weight loss due to the thermal decomposition of the carboxyl and hydrazide groups, with a weight loss of 1.505 mg; within the range of 240-430℃, both VS and JAD showed significant thermogravimetric loss due to varying degrees of carbon chain decomposition, with JAD losing 7.754 mg less than VS. Furthermore, in subsequent comparisons of loss amounts, JAD consistently showed less loss than VS, indicating that the functionalized JAD exhibits stronger thermal stability than VS. The results demonstrate that JAD possesses strong thermal stability.
[0064] ④ Isopotential analysis
[0065] By analyzing Pb 2+ The adsorption of Pb by JAD by the solution at different pH values 2+ Perform an isoelectric experiment and obtain the results (e.g.) Figure 5 The figure shows the isoelectric point diagram of JAD adsorbing metallic lead. It can be seen from the figure that when the solution potential is 0, the corresponding pH value is 2.68, so the isoelectric point of JAD is 2.68. When the solution pH value is greater than 2.68, and as the pH value gradually increases, the absolute value of the isoelectric point also increases. This is because as the solution pH increases, the degree of ionization of JAD itself increases, resulting in an increase in the number of anionic groups such as OH- and COO- on its surface, thereby increasing its binding capacity for cations, and consequently increasing its binding capacity for Pb. 2+ The adsorption capacity demonstrates that JAD has a strong adsorption capacity for metallic lead.
[0066] ⑤ Adsorption-desorption reuse analysis
[0067] After five consecutive adsorption-desorption cycles of JAD, the processed experimental data (e.g.) Figure 6(As shown). After 5 iterations, JAD achieves a certain result for Pb. 2+ The adsorption rate decreased from 97.389% to 69.758%, indicating that within a certain number of cycles, the adsorption rate of JAD gradually decreases with increasing cycles, but it still maintains a reliable adsorption rate. This demonstrates that salicylhydrazine-modified distiller's grains have good durability and reusability. The results of five adsorption-desorption repeated adsorption experiments also show that JAD effectively adsorbs Pb. 2+ The adsorption repeatability is relatively strong, so JAD is an adsorbent that meets the requirements for sustainable recycling.
[0068] ⑥ Adsorption isotherm analysis
[0069] The adsorption rate of lead metal by JAD with different initial concentrations was investigated by conducting adsorption isotherm experiments on lead metal adsorption by JAD. The experimental data were fitted using the Langmuir adsorption isotherm model and the Freundlich adsorption isotherm model. The effect of initial concentration on the adsorption performance of lead metal solution by JAD was studied by model fitting analysis.
[0070] Depend on Figure 7 It can be seen that JAD affects Pb 2+ The equilibrium adsorption amount varies with Pb 2+ The adsorption capacity increases with increasing concentration until it reaches the maximum saturation adsorption capacity, at which point it stabilizes and the rate of increase slows down. This indicates that the adsorption of lead by JAD is inhibited after reaching the maximum saturation capacity. Table 1 shows that JAD adsorbs lead (Pb). 2+ The R² value was 0.865 when using the Langmuir simulation, while it was 0.959 when using the Freundlich model, indicating that JAD adsorbs metal Pb. 2+ The adsorption isotherm experiment fits the Freundlich model more closely, indicating that JAD has a better effect on Pb. 2+ The adsorption tendency is chemisorption, and combined with the fact that n is 3.275, which is greater than 1, it can be proven that the adsorption of lead by JAD is very easy. Calculations show that the maximum fitted adsorption capacity of JAD for lead is 419.44 mg / g, while the actual maximum adsorption capacity of JAD for lead measured in the experiment was 432.8 mg / g. The maximum values obtained from the experiment are very close to the maximum adsorption capacity obtained from the isothermal model fitting, indicating that the isothermal model fits the adsorption of lead by JAD to a very high degree. Furthermore, the data on the maximum adsorption capacity indicate that JAD is also effective against lead (Pb). 2+ Its adsorption effect is very obvious and its adsorption performance is very impressive.
[0071] Table 2 - Pb adsorption by JAD 2+ isothermal parameters
[0072]
[0073] ⑦ Modified distiller's grains on Pb 2+ Adsorption mechanism analysis
[0074] Pb adsorption from JAD 2+ Changes in microstructure before and after, as shown in the scanning electron microscope images ( Figure 2 It can be seen that JAD adsorbs Pb 2 + Subsequently, its microscopic surface underwent significant changes. The JAD surface had a large number of deposits and fewer pores with larger pore sizes, because Pb adsorption was complete. 2+ It coordinates with the acylhydrazone groups on the JAD surface to form a complex, and the newly formed complex promotes Pb 2+ The sedimentation and accumulation of Pb ultimately 2+ The coordination with the acylhydrazone group reaches a dynamic equilibrium, completing the coordination of Pb. 2+ Adsorption.
[0075] Isopotential analysis under different pH conditions revealed that the adsorption isopotential point is 2.68. When the pH is greater than 2.68, the ionization intensity of JAD increases with increasing pH, leading to an increase in the number of negative ion groups such as OH- and COO- on the surface, thereby enhancing the adsorption of Pb. 2+ The adsorption capacity of JAD for metallic Pb demonstrates its ability to adsorb Pb. 2+ The adsorption is accomplished by the combination of anionic and cationic groups.
[0076] Analysis of the EDAX mapping results revealed that the Ca content decreased significantly after adsorption (Table 1), while the Pb content increased, indicating that JAD adsorbs metallic Pb. 2+ Through with Ca 2+ The exchange has been completed.
[0077] ⑧ Adsorption kinetics experimental analysis
[0078] To investigate the adsorption process of lead by JAD, samples were taken at multiple time points from 5 min to 360 min, and the Pb content of JAD was measured at different time points. 2+ The adsorption rate was found to increase with time (e.g., ...). Figure 8 As shown), when the time reaches 300 min, the adsorption removal rate no longer increases or even decreases, indicating that the adsorption has reached saturation. In order to conduct a more comprehensive and in-depth study of the adsorption process, a quasi-first-order kinetic model (PFO) (Formula 3-3) and a quasi-second-order kinetic model (PSO)
[32] (Formula 3-4) were established in the kinetic experiment to study the adsorption of Pb by JAD. 2+ The process is fitted, and its calculation equation is as follows:
[0079] ln(q_e-q_t)=lnq_e-K_1t (3.3)
[0080] t / q_t=1 / (k_2q_e^2)+t / q_e (3.4)
[0081] In the formula:
[0082] qe-JAD adsorption of Pb 2+ Equilibrium adsorption capacity, mg / g;
[0083] qt—the amount of JAD adsorbed at time t, mg / g;
[0084] k1—PFO model rate coefficient, min﹣1;
[0085] k2—PSO model rate coefficient, g / (mg.ln).
[0086] By using experimental data and fitting formulas for the simulation system, relevant dynamic system models (such as...) are plotted. Figure 9 (As shown in the figure). The figure shows that both the PFO and PSO kinetic models fit the parameters of the JAD Pb²⁺ adsorption kinetics experimental data well, with high goodness of fit. However, the goodness of fit of PSO is higher than that of PFO, with a correlation coefficient of 0.999 for PSO and only 0.757 for PFO. Comparing the correlation coefficients of PSO and PFO, it can be seen that the pseudo-second-order correlation coefficient shows a higher fit. The theoretical adsorption value of 96.361 mg / g obtained from the pseudo-second-order formula is also closer to the actual adsorption value obtained experimentally. Therefore, the Pb²⁺ adsorption process of JAD is more consistent with the PSO kinetic model, and the adsorption reaction is more easily affected by chemisorption. This further proves the adsorption of Pb²⁺ by the modified distiller's grains adsorbent. 2+ It is an adsorption reaction mainly based on chemical adsorption.
[0087] Table 3 - Pb adsorption by JAD 2+ kinetic parameters
[0088]
[0089] ⑨ Adsorption thermodynamics experimental analysis
[0090] Thermodynamic experiments are conducted at different temperatures to investigate the effect of temperature on the adsorption of Pb by JAD. 2+ The adsorption performance of JAD is affected, and the adsorption of Pb can also be analyzed and determined. 2+Whether the adsorption reaction can proceed spontaneously and whether the adsorption process is endothermic can be determined. This allows us to derive the conditions under which the modified distiller's grains adsorbent maintains high efficiency and performance. The experimental data are calculated and analyzed using the van der Hoff equation with enthalpy change ΔHθ (KJ / mol), entropy change ΔSθ (J / mol·K), and Gibbs free energy ΔGθ (KJ / mol).
[0091] lnK_T=(ΔS^θ) / R-(ΔH^θ) / RT (3.5)
[0092] ΔG^θ=-RTlnK_T (3.6)
[0093] K_T = q_e / c_e (3.7)
[0094] In the formula:
[0095] The equilibrium adsorption capacity of qe-JAD at adsorption equilibrium, (mg / g);
[0096] Pb at Ce-JAD adsorption equilibrium 2+ Concentration, (mg / L);
[0097] R—molar gas constant, (8.314 kJ / mol)
[0098] T—Absolute temperature (K)
[0099] The Gibbs free energy calculated by the formula is always less than 0, the entropy change is greater than 0, and the enthalpy change is greater than 0 (as shown in Table 3-5). Therefore, it can be determined that JAD adsorbs Pb. 2+ The adsorption behavior of JAD is a spontaneous reaction, and the adsorption process is endothermic. Higher temperatures are more favorable for the adsorption of Pb. 2+ The reason may be that the increased temperature makes the adsorption groups on the JAD surface more active, and the Pb in the solution... 2+ It will also become more active, causing JAD and Pb to... 2+ The probability of binding increases, and the probability of coordination is also greater.
[0100] Table 4 - JAD versus Pb 2+ Adsorption thermodynamic parameters
[0101]
[0102] This method uses distiller's grains as raw material, which is oxidized with sodium periodate, grafted onto aqueous hydrazide, cross-linked with sodium alginate, and finally combined with Ca. 2+The modified distiller's grains adsorbent (JAD) was finally prepared by exchange. Adsorption experiments were conducted using single-factor variables such as pH, temperature, and adsorption time to study the optimal adsorption conditions for lead by JAD. Finally, the adsorption of lead by JAD was determined. 2+ The optimal adsorption pH was 5, the adsorption equilibrium amount was 438.2 mg / g, and the adsorption equilibrium time was 300 min. The kinetics followed a pseudo-second-order kinetic model, indicating that the adsorption reaction was primarily chemical. Based on the analysis and summarization of thermodynamic experimental data, the adsorption effect of JAD on Pb was determined. 2+ Adsorption is a spontaneous endothermic reaction; analysis of Fourier transform infrared (FT-IR) spectra shows that JAD adsorbs metal Pb. 2+ The group is an acylhydrazone group, and it is formed by the acylhydrazone group and Pb. 2+ Adsorption occurs through binding and coordination interactions; SEM and EDAX spectral analysis show that adsorption of Pb occurs on the JAD surface. 2+ Adsorption occurs through the Ca on the JAD surface. 2+ Metal Pb 2+ It is accomplished through replacement.
[0103] For those skilled in the art, numerous modifications and improvements can be made without departing from the inventive concept of this invention. These modifications and improvements should also be considered within the scope of protection of this invention, and will not affect the effectiveness of the invention or the practicality of the patent. The scope of protection claimed in this application shall be determined by the content of its claims, and the specific embodiments described in the specification can be used to interpret the content of the claims.
Claims
1. A method for preparing a modified adsorbent from distiller's grains, characterized in that, Using distiller's grains as raw material, the process involves alkalization, oxidation, cross-linking, and calcium ion exchange with the cross-linked material; including the following steps: S1. Alkalization of distiller's grains: Take 200-300 g of distiller's grains powder, prepare 1-1.5 L of 0.1-0.2 mol / L NaOH solution and add it to the distiller's grains powder. Stir at a constant temperature of 45-50℃ for 6-7 h. Then add concentrated hydrochloric acid to adjust the pH to 7. Discard the supernatant, wash the precipitate until neutral and centrifuge. Discard the supernatant again, take out the precipitate, dry it at 45-50℃, and grind it into powder to obtain alkalized distiller's grains. S2. Oxidation of distiller's grains: Mix 10-20 g of alkalized distiller's grains with 50-100 mL of anhydrous ethanol and stir at 45-50℃ for 1-1.5 h to obtain an alkalized distiller's grains solution; prepare a sodium periodate solution by adding 5-10 g of sodium periodate to 50-100 mL of distilled water; add the sodium periodate solution dropwise to the alkalized distiller's grains solution and stir; then adjust the pH to 4.0 with hydrochloric acid and stir at 45-50℃ for 24-36 h; then add 5-10 mL of ethylene glycol and stir before filtration to remove the solid; wash the residue after filtration with 50-100 mL of anhydrous ethanol to obtain oxidized distiller's grains; S3. Modification of distiller's grains: Take 2-5g of oxidized distiller's grains and add 30-50mL of anhydrous ethanol and stir for 2-3h. Then add 2-3g of salicylhydrazine and add glacial acetic acid as a catalyst. Stir at 45-50℃ for 24-36h. Then filter and air dry to obtain modified distiller's grains. S4. Crosslinking of distiller's grains: Add 0.5-0.8g of sodium alginate to 100-150 mL of distilled water, then add 2-3g of modified distiller's grains and stir thoroughly. Then add 1-2mL of BDE crosslinking agent and stir for 12-15 hours. Freeze for 24-48 hours and then freeze dry under vacuum to prepare the crosslinked product of acylhydrazone-crosslinked sodium alginate. S5. Crosslinking and calcium ion exchange: The crosslinking material is added to a calcium chloride solution with a mass fraction of 3-5% and stirred for 12-24 hours. After freezing and vacuum drying, the modified adsorbent of distiller's grains is obtained.
2. The method for preparing the modified adsorbent from distiller's grains according to claim 1, characterized in that, In step S2, the alkalized distiller's grains and anhydrous ethanol are stirred in a light-protected environment, and the sodium periodate solution is prepared by stirring in a light-protected environment.
3. The method for preparing the modified adsorbent from distiller's grains according to claim 2, characterized in that, The constant temperature stirring uses a constant temperature magnetic stirrer.
4. The method for preparing the distillers' grains modified adsorbent according to claim 3, characterized in that, After adding hydrochloric acid to adjust the pH in S2, the pH should be maintained at 4.0 during the constant temperature stirring process.
5. The method for preparing the distiller's grains modified adsorbent according to claim 4, characterized in that, The filtration was performed using a Buchner funnel.
6. The method for preparing the modified adsorbent from distiller's grains according to claim 5, characterized in that, The freezing time in S5 is 12–24 h, and the vacuum drying time is 24–48 h.
7. The application of the modified distillers' grains adsorbent prepared according to any one of claims 1 to 6 in the adsorption of heavy metals.
Citation Information
Patent Citations
Cellulose nanocrystalline water / aerogel and preparation method thereof
CN111205483A